Sentinel Nodes in Vulvar Cancer: Long-Term Follow-up of the Groningen International Study on Sentinel Nodes in Vulvar Cancer (GROINSS-V) I. Issue 3 (March 2016) - te Grootenhuis, N. C.; van der Zee, A. G. J.; van Doorn, H. C.; van der Velden, J.; Vergote, I.; Zanagnolo, V.; Baldwin, P. J.; Gaarenstroom, K. N.; van Dorst, E. B.; Trum, J. W.; Slangen, B. F. M.; Runnebaum, I. B.; et al.
Abstract : Obstet Gynecol Surv 2016;71(3):157–159 Treatment for early-stage vulvar cancer used to consist of wide local excision of the tumor combined with an inguinofemoral lymphadenectomy. This treatment is effective but has a high morbidity rate.